Elevating Thai Massage Therapists’ Self Development Needs for Success on Phuket’s Beaches - Teerapattrakul, Ratriya (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2024)
This qualitative study examines the personal development needs of Thai massage therapists operating in the health-oriented beach context of Phuket. The research objectives include understanding the therapists' challenges, identifying their requirements for growth, exploring methods for personal development, and establishing a comprehensive guideline for their enhancement. Data collection involves in-depth observations and interviews, employing triangulation for rigor. The study involves 72 participants: experienced Thai massage therapists working on Phuket's beaches and the chief Thai massage therapist. Data analysis follows a descriptive analytical approach. The findings revealed that the therapists, often elderly among the aged of 35-65 years with massage experience, confront issues like language barriers and lack of professional licensing. Their developmental needs encompass improving their understanding of massage benefits, precautions, emotional management, language proficiency (especially English and Russian), ethical considerations, and product marketing. Personal development strategies include training, site visits, and peer learning. These approaches contribute to a holistic skill set enhancement.